Expanding the genetic landscape of oral‐facial‐digital syndrome with two novel genes. Issue 8 (15th June 2021) - Strong, Alanna; Simone, Laurie; Krentz, Anthony; Vaccaro, Courtney; Watson, Deborah; Ron, Hayley; Kalish, Jennifer M.; Pedro, Helio F.; Zackai, Elaine H.; Hakonarson, Hakon
Abstract: Oral‐facial‐digital syndromes (OFDS) are a heterogeneous and rare group of Mendelian disorders characterized by developmental abnormalities of the oral cavity, face, and digits caused by dysfunction of the primary cilium, a mechanosensory organelle that exists atop most cell types that facilitates organ patterning and growth. OFDS is inherited both in an X‐linked dominant, X‐linked recessive, and autosomal recessive manner. Importantly, though many of the causal genes for OFDS have been identified, up to 40% of OFD syndromes are of unknown genetic basis. Here we describe three children with classical presentations of OFDS including lingual hamartomas, polydactyly, and characteristic facial features found by exome sequencing to harbor variants in causal genes not previously associated with OFDS. We describe a female with hypothalamic hamartoma, urogenital sinus, polysyndactyly, and multiple lingual hamartomas consistent with OFDVI with biallelic pathogenic variants in CEP164, a gene associated with ciliopathy‐spectrum disease, but never before with OFDS. We additionally describe two unrelated probands with postaxial polydactyly, multiple lingual hamartomas, and dysmorphic features both found to be homozygous for an identical TOPORS missense variant, c.29 C>A; (p.Pro10Gln). Heterozygous TOPORS pathogenic gene variants are associated with autosomal dominant retinitis pigmentosa, but never before with syndromic ciliopathy. Of note, both probands are of Dominican ancestry, suggesting a possible founder allele.